Combined Effect of Hydrotherapy and Al-Kahfi Murottal Recitation on Blood Pressure in Elderly Hypertensive Patients (International Forum of Researchers and Lecturers, 2024)
Background: Hypertension is a prevalent health issue among older adults, significantly increasing their risk of mortality. Hydrotherapy, in conjunction with the recitation of Surah Al-Kahfi (a chapter from the Quran), offers a non-pharmacological approach to blood pressure management. This combined therapy is believed to reduce stress hormones and stimulate the release of endorphins, contributing to blood pressure reduction. This study aimed to investigate the effect of this combined therapy on blood pressure in older adults with hypertension. Methods: A pre-experimental, one-group pre- and post-test design was employed. Participants were recruited using purposive sampling. The study population comprised older adults aged 60-70 years with blood pressure ≥ 140/90 mmHg. Blood pressure measurements were taken using a digital sphygmomanometer, and a standardized operating procedure (SOP) was followed for all interventions. Data was analyzed using the Paired Sample T-test. Results: The findings revealed a statistically significant difference in both systolic and diastolic blood pressure before and after the intervention (p = 0.000). The mean difference in systolic blood pressure was 14.1 mmHg, and the mean difference in diastolic blood pressure was 8.4 mmHg. Conclusion: The combined therapy of hydrotherapy and recitation of Surah Al-Kahfi effectively reduces blood pressure in older adults with hypertension. These findings encourage further exploration of this non-pharmacological approach in managing hypertension among older adults.